Curricular Innovation and Digitsation at a Mega University in the Developing World – The UNISA “Signature Course” Project - Narend Baijnath (Commonwealth of Learning, 2013)
As part of the endeavor to reposition itself in the open distance and e-learning arena, the University of South Africa has designed and developed six modular courses (one module per College) referred to as ‘Signature Courses’. The focus of these modules is on a student-centred online teaching and learning approach; extensive student online mentoring and support; and alternative online assessment practices, while also developing prototypes for fully online courses as the University advances in its digitisation objectives. This paper presents a case study of the achievements of the project thus far. It reports challenges the project has been facing and anticipates the trajectory the University will be following in the future as it moves decisively towards online teaching and learning.